2011
DOI: 10.1186/1471-213x-11-40
|View full text |Cite
|
Sign up to set email alerts
|

SOX10 directly modulates ERBB3 transcription via an intronic neural crest enhancer

Abstract: BackgroundThe ERBB3 gene is essential for the proper development of the neural crest (NC) and its derivative populations such as Schwann cells. As with all cell fate decisions, transcriptional regulatory control plays a significant role in the progressive restriction and specification of NC derived lineages during development. However, little is known about the sequences mediating transcriptional regulation of ERBB3 or the factors that bind them.ResultsIn this study we identified three transcriptional enhancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 49 publications
3
30
0
Order By: Relevance
“…Often, intronic regions contain enhancer elements that can greatly influence transcription (4, 25, 26). In addition, the only apparent FOXD3 consensus site in either FOXD3-enriched TWIST1 region was located in intron 1.…”
Section: Resultsmentioning
confidence: 99%
“…Often, intronic regions contain enhancer elements that can greatly influence transcription (4, 25, 26). In addition, the only apparent FOXD3 consensus site in either FOXD3-enriched TWIST1 region was located in intron 1.…”
Section: Resultsmentioning
confidence: 99%
“…There is scarce information on how these signaling molecules and receptors are controlled by the migratory neural crest GRN. Nevertheless, Sox10 seems to play a crucial role and has, forexample, been shown to regulate the expression of neuregulin receptor Erbb3 (Britsch et al, 2001) through an intronic enhancer that is active in migratory neural crest cells (Prasad et al, 2011). Sox transcription factors have also been shown to regulate Robo receptors in other contexts (Samant et al, 2011).…”
Section: Regulatory Interactions In the Migratory Neural Crestmentioning
confidence: 99%
“…ChIP-seq analysis showed that the first intron of ERBB3 was enriched by FOXD3. This region is well conserved between species and functions as an enhancer region for ERBB3 (30)(31)(32). Quantitative PCR (qPCR) showed dramatic enrichment of intron 1 over normal IgG only following FOXD3 expression ( Figure 2B).…”
Section: Identifying the Foxd3 Transcriptome In Melanomamentioning
confidence: 99%